The economic structure and the tertiary ecucation of the function of transformation Hungary 19th and 20th century of in economic integration periods - Köpeczi-Bócz, Tamás; Lőrincz, Mónika (Acta Agraria Debreceniensis, 2016)
Knowledge-intensive businesses sectoral nature of the operation and the specific attributes of the innovation life cycle processes, different needs and different needs induce. These features can also differentiate time that their activities when and what type of resources they require. The availability of capacity in terms of a network co-benefits for those businesses that are creating the possibility that such resources are available to ensure the realization of goals that are not individually owned. These factors and the availability of local availability is also motivated by the small and medium enterprises willingness to cooperate.Regional supply of resources necessary for the operation of the business of insurance, universities play a key role. The functions of universities in innovation as a business service can be understood as an activity that mediate high added value to other organizations and companies. Questions arise as to the innovative nature of the business industry and sector weights would differentiate whether the R&D&Iintensive areas of expertise.